1999
DOI: 10.1099/00207713-49-4-1761
|View full text |Cite
|
Sign up to set email alerts
|

Microbispora corallina sp. nov., a new species of the genus Microbispora isolated from Thai soil

Abstract: T w o actinomycete strains, DF-28 and DF-32T, were isolated from soil samples collected in a deciduous dipterocarp forest in Thailand. They produced longitudinally paired spores on the tips of short sporophores alternately branched from aerial hyphae, and the chemotaxonomic properties of the isolates were the same as those of members of the family Streptosporangiaceae. These phenotypic properties, together with the results of a phylogenetic analysis based on 16s rRNA gene sequences, indicated that these isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
86
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(86 citation statements)
references
References 32 publications
0
86
0
Order By: Relevance
“…PCR-mediated amplification of the 16S rRNA gene and sequencing of the PCR products were carried out as described by Nakajima et al (1999). The 16S rRNA gene sequence of strain RtIII47 T was multiply aligned with related sequences obtained from the GenBank/EMBL/ DDBJ databases using MEGA version 4.0 (Kumar et al, 2008).…”
mentioning
confidence: 99%
“…PCR-mediated amplification of the 16S rRNA gene and sequencing of the PCR products were carried out as described by Nakajima et al (1999). The 16S rRNA gene sequence of strain RtIII47 T was multiply aligned with related sequences obtained from the GenBank/EMBL/ DDBJ databases using MEGA version 4.0 (Kumar et al, 2008).…”
mentioning
confidence: 99%
“…PCR amplification of the 16S rRNA gene was carried out as described by Nakajima et al (1999). Sequencing of the cloned PCR product was done by TsingKe (Beijing, China).…”
mentioning
confidence: 99%
“…The amplification of 16S rRNA gene and nucleotide sequencing of PCR product (Macrogen) was carried out using the methods previously described by Nakajima et al (1999) and the universal primers as reported by Lane (1991). The BLAST analysis of 16S rRNA gene was determined using the EzTaxon-e database (Kim et al, 2012).…”
mentioning
confidence: 99%